The Effect Of The Strategy To Accelerate The Thinking In The Collection Of Second Grade Students And The Development Of Their Sports Culture - Adil Fadhil, Jihan; Hameed Hassn, Maysaa (Opción, 2019)
The aim of this study is to know (the impact of the strategy of accelerating thinking in the achievement of second grade students and the development of their sports culture). Two sections of the second intermediate class were cho- sen in (Makkah Girls) of Nineveh governorate to represent one experimental group which is studying according to (accelerating thinking). The number of students was 33 and the other group is an officer who is studying in a regular way. The number of students (30), and thus the number of individuals sam- ple study (63) students. To achieve the objectives of the study prepared a test of achievement of (40) paragraphs were verified reliability and stability and a measure of sports culture. Data were treated statistically using Spss pro- gram. The results of the study showed that there are statistically significant differences between the average scores of students of both groups in the test of achievement and mathematical culture in favor of an experimental group.